Endovascular management of Critical Limb Ischaemia: Study of 100 Cases - Kabir, Md Humayun; Rahman, Munshi Md Mojibur; Khan, AKM Musa; Idris, Rumman (Cardiovascular Journal, 2019)
Background: Critical limb ischemia (CLI) is the most severe form of Peripheral Artery Disease (PAD) and represents approximately 1% of the total number of patients with PAD. CLI is associated with a higher risk of limb loss in the absence of revascularization. Objectives of the study are to find out the modality of treatment in CLI, different types of endovascular therapy in CLI and their outcome. Methods: A retrospective study evaluated 100 patients with CLI reported to cardiovascular surgery department in Combined Military Hospital (CMH), Dhaka between July 2016 to June 2018. Patients with disabling claudication or rest pain and tissue loss are included in the study. All patients were evaluated by peripheral angiogram and revascularisation of limbs was done by endovascular procedure in 79 patients, by surgical intervention in 12 patients. Results: Forty-four patients (44%) presented with rest pain and disabling claudication, 56 patients (56%) presented with tissue loss. Revascularization of limbs was done in 91 patients (93%). No intervention could be done in 9 patients (9%). Endovascular interventions were done in 79 patients (87%). Twelve patients (13%) underwent surgical bypass. All patients with rest pain remains asymptomatic in 6 months follow up; 2 patients developed reocclusion within 1 year. No major amputation in patients with only rest pain. Conclusion: Revascularization is the main modality of treatment in CLI. Most of the patient can be treated by endovascular percuteneous procedure. Early intervention in CLI patient without tissue loss carries excellent outcome. Cardiovasc. j. 2019; 12(1): 40-44